Pathology and pathogenesis of Brucella melitensis infection in bucks - Nasruddin, Nurrul Shaqinah (2014)
Brucellosis is an important disease of ruminants in many countries, including Malaysia. It is caused by Brucella melitensis leading to serious economic impact to goat farmers following abortions and stillbirths. The infection has not been thoroughly studied in bucks, particularly on the pathological changes and distribution of the organisms in the host. Furthermore, the efficacy of intracellular killing of B. melitensis by exposed bucks and the effectiveness of commonly used serological tests in identifying infected bucks need to be clarified. This study was conducted to observe the pathological changes and pathogenesis in bucks following experimental infection by B. melitensis. Nine clinically healthy crossbred Jamnapari bucks of approximately 12 months old were used. The animals were confirmed as sero-negative for brucellosis following Rose Bengal Precipitation Test (RBPT) and Complement Fixation Test (CFT) tests. The selected bucks were divided into 3 equal groups. Groups 1 and 2 were infected intraconjunctival with 50 μl of an inoculum containing 109 cells/ml live local strain of B. melitensis and were sacrificed on days 7 and 14, respectively. Group 3 were similarly exposed to 50 μl normal saline before they were sacrificed on day 14. Serum samples for RBPT, CFT and ELISA, and conjunctival and prepuce swabs for bacterial isolation were collected at 3-day intervals. During post-mortem examination, the prescapular, submandibular and supramammary lymph nodes, the testis, epididymis, prepuce, seminal vesicle, bulbourethral gland, liver, spleen, conjunctiva and synovial membrane were collected for bacterial isolation and histopathology assessment. Infected bucks developed mild pathological changes at 7 and 14 days post-infection (P.I) but did not demonstrate any clinical sign. There was no significant different (p>0.05) in the severity of pathological changes at days 7 and 14 post-infection. The histopathological lesions included necrotizing orchitis, epididymitis, seminal vesiculitis, hepatitis and phostitis. Nevertheless, immunoperoxidase positive reactions were observed in almost all organs that were sampled. The pathological findings proved that acute brucellosis led to mild histopathological changes even though the antigen was disseminated to all organs. Brucella melitensis was not isolated from prepucial swabs that were collected between days 0 and 9 P.I. Later, isolations were successfully made from 66% of prepucial swabs on day 12 P.I and from 33% of the swabs on day 14 P.I. Isolations from the conjunctival swabs were successful on days 3, 12 and 14 P.I. Approximately 33% and 50% of the synovial membrane samples collected between days 7 and 14 P.I revealed positive isolations, and the synovial membrane was found to be the most suitable sample for isolations of B. melitensis in acutely infected bucks. Nevertheless, polymerase chain reaction (PCR) resulted in highest frequency of detection of B. melitensis and the most consistent results were observed in the testis (100% positive). The in vitro assessments of phagocytosis and intracellular killing of B. melitensis were carried out using 6 healthy crossbred Jamnapari bucks of approximately 12 months of age. They were divided into 2 groups after the animals were tested with RBPT and CFT to ensure the brucellosis free status. The bucks of Group 1 were exposed subcutaneously with 2 ml inoculums containing 109 cells/ml of formalin-killed B. melitensis. The bucks of Group 2 were given 2ml sterile PBS as unexposed control group. Both groups were kept for 14 days before the neutrophil, macrophages and lymphocytes were harvested. The cells were then prepared as cell suspension containing 106 cells/ml in 200 μl in each individual chamber before 200 μl of an inoculum containing 107 cells/ml of live B. melitensis was introduced into the chambers. The extracellular Gram-positive bacterium, Streptococcus agalactiae and Gram-negative bacterium, Pasteurella multocida were used for comparison. The cells were then harvested at 0, 30, 60 and 120 minutes post-incubation and stained with Acridine orange and Crystal violet for viewing under fluorescent microscope to determine the phagocytosis index rate and intracellular killing index. Phagocytosis activity by the neutrophils revealed no significant difference (p>0.05) between 30 and 60 min of incubation as well as between the two animal groups. However, rate of phagocytosis by neutrophils that were derived from exposed bucks was significantly (p<0.05) higher at 120 min. Subsequently, the neutrophils were able to kill 68% of the phagocytosed B. melitensis, which was significantly (p<0.05) lower than the two other extracellular bacteria. Similarly, macrophages from both groups showed no significant difference (p>0.05) in the phagocytosis activities at 30 and 60 min of incubation. However, at 120 min, macrophages that were derived from the exposed group demonstrated significantly (p<0.05) higher rate of phagocytosis. On the other hand, penetration of B. melitensis into lymphocytes of bucks revealed that B. melitensis was able to penetrate but was unable to survive long in the cells. The study proved the capability of B. melitensis to invade the lymphocytic cells, which enhanced movement of the organism within the body without triggering immunological response. Nevertheless, B. melitensis lacked replication capabilities in the lymphocytes. In this study, sera from infected and uninfected bucks were processed to determine the antibody levels using ELISA and the two standard screening tests; the RBPT and the CFT. The RBPT and CFT assays provided negative results for all sera collected throughout the 14-day experiment. Meanwhile, ELISA revealed significantly (p<0.05) increased IgG level postinfection. However, the IgA levels in conjunctiva and prepuce showed fluctuating patterns and peaked on day 6 P.I. Therefore, RBPT and CFT were found to be less useful for detection of acute brucellosis while ELISA would be a better test to be used for acute caprine brucellosis.